FIGURE OF SPEECH REPRESENTING RELIGIOUS EDUCATION VALUES IN MOUSTAFA AKKAD’S THE MESSAGE - Sara Mostafa Shokshok; Rohmani Nur Indah (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
Figure of speech used in literary writing touches feelings, emotions based on an image of things seen, and actions experienced. When it applies to the language in a movie, it may furnish new effects or fresh insights into an idea or a subject. This study explored the figure of speech representing religious education values in Moustafa Akkad's The Message movie. As qualitative descriptive research, the source of data was the script of the movie analyzed from the sociolinguistic point of view. The result shows that the film used the figurative language to express religious education values through irony, simile, personification, paradox, hyperbole, oxymoron, metaphor, repetitive, metonymy, antithesis, onomatopoeia, and symbol.  Also, Moustafa Akkad presented several religious values applicable to teaching English for Islamic Studies.